European Witchcraft and Haitian Voodoo - Medrano Marqués, Manuel Mª (Historiografías, 2025)
The influence of European witchcraft in Haitian Voodoo shows a very high intensity within the set of components of this magical-religious system. Thus, one of the main spells of Haitian Voodoo, les expéditions or l'envoi morts, has clear references in the practices carried out previously in the Iberian Peninsula and the Canary Islands but also in ancient Rome. The magic-religious tradition of Europe is shown to be determinant in the case of magic dolls, as evidenced by the rituals present in the Canary Islands with origins in the Iberian Peninsula as well as the influence of the English poppets. The zombies undergo a transmutation, they wake up when they taste salt, saving their soul, recovering it, in a similar way to how this element was used in the European Middle Ages. The loups-garous, vampire witches that suck children, are an almost exact version of the Strix of the Greco-Roman world, beings that continue to appear in the European and Near Eastern cultural sphere in the following centuries, and that were reflected by the painter Francisco de Goya in several works. These witches metamorphose into animals, both in Visigothic Spain and in Spain from the 16th to the 19th centuries, as well as in Haiti. Finally, the “power of the eyes” is seen in the witches of northwestern Spain and in the Haitian hungan and mambo, in a very similar way.KeywordsEuropean Witchcraft, Haitian Voodoo, Vampire witches, Magic dolls, Eye power, Zombie